2018
DOI: 10.2139/ssrn.3168255
|View full text |Cite
|
Sign up to set email alerts
|

Change in Time Preferences: Evidence from the Great East Japan Earthquake

Abstract: This study examines whether individuals' time preferences are affected by the damage resulting from the tsunami in the Great East Japan Earthquake of 2011, using panel surveys before and after the earthquake. When the change in time preferences is measured using the (β, δ) model, I find that the present bias tendency is increased (shrinking β), although the change in the time discount rate (δ) is not statistically significant for those affected by the tsunami. This study also investigates changes in time prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The sample selection for long-term analysis is conducted in a similar way. 21 We merge the JHPS-CPS data with the earthquake intensity data at the municipality level because the municipality is the most detailed unit of location available in the JHPS-CPS. Table 2 presents the summary statistics of our final sample.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sample selection for long-term analysis is conducted in a similar way. 21 We merge the JHPS-CPS data with the earthquake intensity data at the municipality level because the municipality is the most detailed unit of location available in the JHPS-CPS. Table 2 presents the summary statistics of our final sample.…”
mentioning
confidence: 99%
“…20 The reasons for attrition in 2012 and 2016 surveys are as follows (however, breakdown by gender is not available): refused (51.3 percent and 50.3 percent), moved away (22.9 percent and 18.2 percent), temporarily absent (7.2 percent and 4.9 percent), and others (18.6 percent and 18.9 percent). 21 We start with 3,040 subjects with no missing values for the lottery question, risk-taking behavior, age, gender, and household income in both 2011 and 2016 surveys. We then eliminate 427 respondents who were dropped from the short-run analysis.…”
mentioning
confidence: 99%
“…The dynamically inconsistent preference, or present bias, has been previously reported to be associated with behaviors such as smoking and unhealthy eating [28,29]. Our single-choice experiment in the present study did not allow us to differentiate between these two discount rates, although previous studies have reported that present bias (β) in adults, but not δ discount rates were affected by the Great East Japan Earthquake [14,15]. The finding of the present study suggests that children who suffered housing loss were more impatient which can be attributed to either or both of these two discount rates.…”
Section: Plos Onementioning
confidence: 67%
“…Previous studies reported that disasters could influence the behavioral preferences of grown-ups [14][15][16]. In the case of the Great East Japan Earthquake, Akesaka employed nationwide panel data before and after the disaster and reported that present bias or hyperbolic discounting-the extent that discounting rate becomes steeper when it comes to choices in the near future (so-called β discounting)increased for adults living in tsunami-damaged municipalities while discount factor consistent over time or exponential discounting (δ discounting) did not significantly change [15]. Sawada et al also reported that the severity of housing damage in the disaster was associated with stronger present bias among older people [14,16].…”
Section: Introductionmentioning
confidence: 99%
“…All Option B amounts were as follows: THB 330, THB 306, THB 594, THB 303, THB 312. We followed the methods for finding discount rates used in Ikeda et al (2010) and Akesaka (2018), where the discount rate is the interest rate at which participants switch from choosing Option A to Option B [42,43]. For example, a participant who selected Option A for THB 303, THB 306, THB 312, and THB 330 (interest rate of 521%) but selected Option B for THB 594 (interest rate of 5110%) was assigned a discount rate of 521%.…”
Section: Time Discountingmentioning
confidence: 99%